If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 2) * 2 + -4 = 12 Reorder the terms: 4(2 + x) * 2 + -4 = 12 Reorder the terms for easier multiplication: 4 * 2(2 + x) + -4 = 12 Multiply 4 * 2 8(2 + x) + -4 = 12 (2 * 8 + x * 8) + -4 = 12 (16 + 8x) + -4 = 12 Reorder the terms: 16 + -4 + 8x = 12 Combine like terms: 16 + -4 = 12 12 + 8x = 12 Add '-12' to each side of the equation. 12 + -12 + 8x = 12 + -12 Combine like terms: 12 + -12 = 0 0 + 8x = 12 + -12 8x = 12 + -12 Combine like terms: 12 + -12 = 0 8x = 0 Solving 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '8'. x = 0 Simplifying x = 0
| 2(x+7)=10 | | 9x^2+3kx-k=0 | | x^2-6x+3=k(2x-1) | | 15-5x=-25 | | 3x-9=42 | | 42-20=2p | | 3y^2-4=4y | | -4x-40-14x=32 | | C=Amt | | C=Amy | | x-x*0.2=y | | 3x^2-14x=5 | | 4k(k+3)=-19 | | 3-2=x+4 | | 5x+2(x+2)=18 | | 6x^2+11x=72 | | 4x^2-44x=-120 | | 3x+6=X+4 | | C=2500+0.5Yd | | 14+8.2= | | -2j+5=6h | | 3u-(25-u)=-11-2u | | Y=3mx-4b | | t^4-13t^2+36=0 | | (x-1)(2x+1)=0 | | 320=24+20 | | x^2+28x+5=0 | | y^2+16y+28=0 | | 6x^2-9-13x^2+11+11x= | | 3p+3=14 | | 12+(34-5)= | | 3(x+8)=15 |